Early life stress alters pituitary growth during adolescence—A longitudinal study. (March 2015) - Ganella, Despina E.; Allen, Nicholas B.; Simmons, Julian G.; Schwartz, Orli; Kim, Jee Hyun; Sheeber, Lisa; Whittle, Sarah
Highlights: Childhood maltreatment predicted accelerated PGV development in females. Maternal dysphoric behavior predicted accelerated PGV growth in the whole sample. Adverse childhood experience may alter PGV growth by affecting HPA axis function. Abstract: The pituitary gland is integral in mediating the stress-response via its role in hypothalamic–pituitary–adrenal (HPA) axis function. Pituitary gland volume (PGV) is altered in stress-related psychopathology, and one study to date has shown stress to be associated with age-related PGV change during adolescence. The current study investigated the effects of a number of different types of early life (i.e., childhood and adolescent) stress (including childhood maltreatment, stressful life events, and maternal affective behavior) on PGV development from mid- to late adolescence using a longitudinal design. The influence of PGV development on depressive and anxiety symptoms was also investigated. Ninety one (49 male) adolescents took part in mother-child dyadic interaction tasks when they were approximately 12 years old, reported on childhood maltreatment and stressful life events when they were approximately 15 years old, and underwent two waves of structural magnetic resonance imaging (MRI) scans, when they were approximately 16 and 19 years old. Results revealed that childhood maltreatment predicted accelerated PGV development in females, and maternal dysphoric behavior predicted accelerated PGV development in the whole sample. PGV development was not associated with depressive or anxiety symptoms. These results suggest an effect of early life stress on altered HPA axis function across mid- to late adolescence. Further research is required to assess functional implications and whether these changes might be associated with risk for subsequent psychopathology.